The public-private partnerships' impact on transparency and effectiveness in the EU internet content regulation: The Case of "Network Enforcement Act (NetzDG)" in Germany - Jieum Park (Universitätsverlag Potsdam, 2020)
This master's thesis examined the internet content regulation in Germany from a perspective of Public-Private Partnerships. In the European Union, there has been a latest trend of initiatives aiming for combating illegal content online under the self-regulatory regime. Yet, concerns of this trend were that transparency cannot be ensured properly to safeguard the freedom of expression, and that the private intermediaries are not able to carry out effective regulation under the non-binding regulatory process. Due to these issues, Germany has legislated the Network Enforcement Act in 2017. This thesis used Mixed Methods within a Case Study Research, in order to identify the PPP type of the NetzDG, and to understand its link on transparency and effectiveness, as well as the relationship of these two dimensions. By taking an Exploratory Sequential Design, the German internet content regulation under the NetzDG was explored to understand its co-regulatory regime and to develop an instrument to measure the aspects of transparency and effectiveness. Then, the three big social media platforms, YouTube, Twitter, and Facebook, were examined according to the developed indicators. This thesis concluded as follow: First, the enactment of the NetzDG brought the shift of the regulatory paradigm from the self-regulatory to the co-regulatory. Yet, the actor-inclusive institutional arrangement of the NetzDG did not successfully result in the actual inclusion of actors in decision-making, but only improved the result transparency in the disclosure of take-down actions. Second, the level of effective regulation was not consistent across the three social media platforms under this regime. Despite these limitations, this study showed that the transparency and the effectiveness of the social media platforms' implementation gradually improved together, instead of having a negative correlation to one another. – – Diese Masterarbeit untersucht die Regulierung von Internetinhalten in Deutschland aus der Sicht von Public-Private Partnerships. In der Europäischen Union hat es in letzter Zeit einen Trend zu Initiativen zur Bekämpfung illegaler Internetinhalte im Rahmen der Selbstregulierung gegeben. Jedoch besteht die Sorge, dass weder Transparenz richtig gewährleistet werden kann, um die Meinungsfreiheit zu schützen, noch dass es für Social Media Plattformen nicht möglich ist, die Regulierungen in einem unverbindlichen Selbstregulierungssystems effektiv durchzusetzen. Aufgrund dieser Probleme verabschiedete Deutschland 2017 das Netzwerkdurchsetzungsgesetz (NetzDG). Diese Masterarbeit nutzt einen Mixed Methods-Ansatz im Rahmen einer Fallstudie, um die Art von Public-Private Partnerships des NetzDG zu bestimmen und um ihre Verbindung zu Transparenz und Effektivität sowie deren Beziehung untereinander zu verstehen. Durch ein exploratives sequentielles Forschungsdesign wurde die deutsche Regulierung von Internetinhalten unter dem NetzDG untersucht, um das ko-regulierende System zu verstehen und um Instrumente zur Messung von Transparenz- und Effektivitätsaspekten zu entwickeln. Dabei wurden die drei großen Social Media Plattformen (YouTube, Twitter und Facebook) in Bezug auf die entwickelten Indikatoren analysiert. Basierend auf den Ergebnissen kommt diese Masterarbeit zu folgenden Schlüssen: Erstens, brachte das Inkrafttreten des NetzDGs einen Wandel des Regulierungsregimes von der Selbstregulierung zur Ko-Regulierung. Die akteurs-übergreifende institutionelle Ausgestaltung des NetzDG führte zwar zu keiner tatsächlichen Einbeziehung der Akteure in die Entscheidungsfindung, sondern hat lediglich die Ergebnistransparenz bei der Offenlegung von Take-down Handlungen verbessert. Zweitens war in den verglichenen drei Social Media Plattformen das Niveau der effektiven Regulierung nicht einheitlich. Trotz dieser Einschränkungen zeigt diese Studie, dass sich die Transparenz und die Effektivität der Umsetzung des NetzDGs durch die Social Media Plattformen gemeinsam sukzessive verbessert haben, statt in einem Trade-off Verhältnis zueinander zu stehen.
urn:nbn:de:kobv:517-opus4-487183
Keywords: 650; Internet Content Regulation; Network Enforcement Act; Transparency; Effectiveness; Public-Private Partnerships; Co-Regulation; Regulierung von Internetinhalten; Netzwerkdurchsetzungsgesetz; Transparenz; Effektivität; Öffentlich-Privater-Partnerschaften; Ko-Regulierung